2012
DOI: 10.1614/wt-d-11-00059.1
|View full text |Cite
|
Sign up to set email alerts
|

Management of Italian Ryegrass (Lolium perennessp.multiflorum) in Western Oregon with Preemergence Applications of Pyroxasulfone in Winter Wheat

Abstract: Management of Italian ryegrass in cereal-based cropping systems continues to be a major production constraint in areas of the United States, including the soft white winter wheat producing regions of the Pacific Northwest. Pyroxasulfone is a soil-applied herbicide with the potential to control broadleaf and grass weed species, including grass weed biotypes resistant to group 1, 2, and 7 herbicides, in several crops for which registration has been completed or is pending, including wheat, corn, sunflower, dry b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
36
1
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 43 publications
(43 citation statements)
references
References 16 publications
3
36
1
1
Order By: Relevance
“…Pyroxasulfone's soil residual activity and utility have allowed it to be registered for multiple uses including corn (field, sweet, and pop) (Zea mays L.), soybean, cotton, fallow land, and non-crop areas [47][48][49]. Winter wheat tolerance has been well documented with only minor injury in the form of stunting with no negative effects on yield [50][51][52]. With PRE soil activity on broadleaf and grass species including ALS- [52], ACCase- [41], and glyphosate- [1] resistant Italian ryegrass biotypes, pyroxasulfone use in wheat will afford growers an early season weed control option that was previously unavailable.…”
Section: Soil Residual Herbicidesmentioning
confidence: 99%
See 1 more Smart Citation
“…Pyroxasulfone's soil residual activity and utility have allowed it to be registered for multiple uses including corn (field, sweet, and pop) (Zea mays L.), soybean, cotton, fallow land, and non-crop areas [47][48][49]. Winter wheat tolerance has been well documented with only minor injury in the form of stunting with no negative effects on yield [50][51][52]. With PRE soil activity on broadleaf and grass species including ALS- [52], ACCase- [41], and glyphosate- [1] resistant Italian ryegrass biotypes, pyroxasulfone use in wheat will afford growers an early season weed control option that was previously unavailable.…”
Section: Soil Residual Herbicidesmentioning
confidence: 99%
“…The soils for the present studies were a sandy loam, loamy sand, or sandy clay loam with less than 2.0% organic matter. Hulting et al [52] noted 3% or less wheat injury from pyroxasulfone rates up to 100 g ha −1 on a silt loam soil. Previous research indicated decreased pyroxasulfone injury with legumes grown in soils with greater clay contents [19].…”
Section: Crop Response and Weed Controlmentioning
confidence: 99%
“…Pyroxasulfone applied at rates between 60 and 180 g ai/ha has been documented to control: Amaranthus spp., Lolium spp., Urochloa spp., goosegrass (Eleusine indica L.), crowfootgrass (Dactyloctenium aegyptium L), and Digitaria spp. (Geier et al 2006;Hulting et al 2012;King and Garcia 2008;Koger et al 2008;Knezevic et al 2009;Nurse et al 2011).…”
mentioning
confidence: 99%
“…Pyroxasulfone use in corn, cotton (Gossypium hirsutum L.), soybean, and wheat (Triticum aestivum L.) tolerance has been thoroughly described (Cahoon et al 2012;Eure et al 2013;Geier et al 2006;Hulting et al 2012;King and Garcia 2008;Koger et al 2008). However, very little is known concerning peanut response to pyroxasulfone following PRE applications.…”
mentioning
confidence: 99%
“…Pyroxasulfone provides residual control of troublesome annual broadleaf weeds and grasses, including; browntop millet (Urochloa ramose L.), barnyardgrass (Echinochloa crus-galli L.), green foxtail (Setaria viridis L.), Amaranthus spp., velvetleaf (Abutilon theophrasti Medik. ), large crabgrass (Digitaria sanguinalis L.), Italian ryegrass (Lolium multiflorum L.), and kochia (Kochia scoparia L.) (Geier et al 2006;Gregory et al 2005;Hulting et al 2012;King and Garcia 2008;Koger et al 2008;Nurse et al 2011). Pyroxasulfone applied at 209 g ai/ha controlled broadleaf signalgrass (Urochloa platyphylla L.) similar to dimethenamid-p and S-metolachlor; however, dimethenamid-p and S-metolachlor provide poor residual control of Texas millet (Urochloa texana Buckl.)…”
mentioning
confidence: 99%